Circulating serum profile of small non-coding RNAs in patients with anaphylaxis beyond microRNAs - Sergio Fernández-Bravo; Diana Betancor; Javier Cuesta-Herranz; Pablo Rodríguez del Río; María Dolores Ibañez-Sandín; Emilio Nuñez-Borque; Vanesa Esteban; Vanesa Esteban (Frontiers in Allergy, 2024)
IntroductionAnaphylaxis is the most severe manifestation of allergic disorders. Currently, an increasing number of cells, pathways and molecules involved in the etiopathogenesis of anaphylaxis are being discovered. However, there are no conclusive biomarkers to confirm its diagnosis. Small non-coding RNAs (sncRNAs) are 18-200 nucleotide molecules that can be divided into: microRNAs (miRNAs), Piwi-interacting RNAs (piRNAs), small nucleolar RNAs (snoRNAs), small nuclear RNAs (snRNAs), transference RNA derived fragments (tRFs) and YRNA derived fragments (YRFs). These molecules participate in cell-cell communication modulating various physiological processes and have been postulated as non-invasive biomarkers of several pathologies. Therefore, in this study we characterized the serum circulating profile of other sncRNA beyond miRNAs in two populations of 5 adults and 5 children with drug- and food-mediated anaphylaxis, respectively.MethodsSamples were obtained from each patient under two different conditions: during anaphylaxis and 14 days after the reaction (control). The sncRNA analysis was carried out by Next Generation Sequencing (NGS).ResultsA total of 671 sncRNAs (3 piRNAs, 74 snoRNAs, 54 snRNAs, 348 tRFs and 192 YRFs) were identified in adults with drug-induced anaphylaxis, while 612 sncRNAs (2 piRNAs, 73 snoRNAs, 52 snRNAs, 321 tRFs and 164 YRFs) were characterized in children with food-mediated anaphylaxis. However, only 33 (1 piRNA, 4 snoRNAs, 1 snRNAs, 7 tRFs and 20 YRFs) and 80 (4 snoRNAs, 6 snRNAs, 54 tRFs and 16 YRFs) of them were statistically different between both conditions, respectively. Among them, only three (Y_RNA.394, Y_RNA.781 and SCARNA2) were common to both adults and children analysis.DiscussionThis study provides a differential profile of circulating serum sncRNAs beyond miRNAs in patients with anaphylaxis, postulating them as candidate biomarkers for this pathological event and as novel mediators of the reaction.